2021
DOI: 10.2147/cmar.s305946
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXA-AS2 Promotes Tumor Progression by Suppressing miR-567 Expression in Oral Squamous Cell Carcinoma

Abstract: Introduction: Growing evidence suggests that long non-coding RNAs (lncRNAs), such as lncRNA HOXA-AS2, are critical regulators involved in human cancer. However, the biological functions and detailed mechanisms underlying how lncRNA HOXA-AS2 affects oral squamous cell carcinoma (OSCC) remain unexplored. Methods: The expression of lncRNA HOXA-AS2 and miR-567 was determined in OSCC cell lines and clinical tissues by quantitative real-time PCR (qRT-PCR). Target site prediction and luciferase report assays were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“… 35 Many studies have demonstrated lncRNAs involved in competitive regulatory interactions and can act as microRNA decoys to modulate gene expression, which is known as ceRNA. 36 , 37 In this study, lnc DRAIC has potential binding sites with miR-3940-3p, and the siRNA of lnc DRAIC can significantly increase the expression level of miR-3940-3p. Dual-luciferase reporter assay confirmed the binding between lnc DRAIC and miR-3940-3p.…”
Section: Discussionmentioning
confidence: 72%
“… 35 Many studies have demonstrated lncRNAs involved in competitive regulatory interactions and can act as microRNA decoys to modulate gene expression, which is known as ceRNA. 36 , 37 In this study, lnc DRAIC has potential binding sites with miR-3940-3p, and the siRNA of lnc DRAIC can significantly increase the expression level of miR-3940-3p. Dual-luciferase reporter assay confirmed the binding between lnc DRAIC and miR-3940-3p.…”
Section: Discussionmentioning
confidence: 72%
“…CDK3 has been reported to promote myoblast cell proliferation; 31 Yue et al showed that CDK5 promotes the proliferation of medullary thyroid carcinoma cells; 32 in addition, Chen et al showed that the promotion of OSCC cell proliferation by direct binding of miR-567 leads to increased CDK8 expression. 33 These previous findings suggest that CDK3, CDK5 and CDK8 is an oncogene.…”
Section: Discussionmentioning
confidence: 86%
“…A total of 18 articles including 1181 patients were included, and the cancer types included gastric cancer ( 24 ), colorectal cancer (CRC) ( 29 , 40 ), hepatocellular carcinoma(HCC) ( 26 , 27 , 41 ), breast cancer ( 18 ), non-small cell lung cancer (NSCLC) ( 19 , 22 ), prostate cancer ( 31 ), osteosarcoma ( 36 , 37 ), bladder cancer ( 30 ), oral squamous cell carcinoma (OSCC) ( 13 ), papillary thyroid cancer (PTC) ( 15 , 16 ), cervical cancer ( 35 ) and glioma ( 47 ). The publication years were from 2015 to 2021, and all patients were from China.…”
Section: Resultsmentioning
confidence: 99%
“…HOXA-AS2 is a 1048-bp long noncoding RNA located on human chromosome 7p15.2 between the HOXA3 and HOXA4 genes in the HOXA cluster ( 11 ). In recent years, an increasing number of publications have shown that HOXA-AS2 is highly expressed in diverse malignancies, including oral squamous cell carcinoma ( 12 , 13 ), nasopharyngeal carcinoma ( 14 ), thyroid cancer ( 15 , 16 ), breast cancer ( 17 , 18 ), lung cancer ( 19 – 22 ), gallbladder carcinoma ( 23 ), gastric cancer ( 24 , 25 ), hepatocellular carcinoma ( 26 , 27 ), pancreatic cancer ( 28 ), colorectal cancer ( 29 ), bladder cancer ( 30 ), prostate cancer ( 31 ), ovarian cancer ( 32 ), endometrial cancer ( 33 ), cervical cancer ( 34 , 35 ), osteosarcoma ( 36 , 37 ) and glioblastoma ( 38 ). Cell function tests showed that high HOXA-AS2 expression can promote the proliferation and invasion of cancer cells, inhibit apoptosis, and affect the cancer cell cycle ( 21 , 32 ).…”
Section: Introductionmentioning
confidence: 99%